Net zero export finance: Lessons for Austria from international best practice - Lukas Schlogl; David Pfaffenbichler; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2024)
This study investigates the intersection of export finance and climate policy with a focus on Austria and relevant peers. It addresses the role of Austria's export credit system in facilitating the global transition to a net-zero economy. Specifically, it examines how Austria's official export financing policy aligns with the goals of the Paris Agreement and explores ways to reform it towards promoting a more sustainable and climate-neutral portfolio. Public export promotion policies and so-called export credit agencies (ECAs) have a significant potential to leverage change: They are based on powerful financial instruments that provide government-backed loans, guarantees, and insurance for international trade. Their influence extends globally as they reduce the risk of international business transactions and encourage economic activities abroad. However, these financial institutions have traditionally supported carbon-intensive projects, such as those in the fossil fuel sector, significantly contributing to greenhouse gas (GHG) emissions. Given the urgency of the climate crisis, as highlighted by the Intergovernmental Panel on Climate Change (IPCC), there is increasing global pressure on governments and ECAs to align their activities with the Paris Agreement. This alignment is essential for limiting dangerous global warming to 1.5êC, as outlined by the International Energy Agency (IEA), which asserts that new fossil fuel projects must be avoided to meet these targets. Austria, like many other countries, is at a critical juncture where its export credit policies must pivot quickly and decisively towards climate sustainability. Austria's export credit portfolio, while relatively small compared to international peers, still contains exposure to fossil fuel projects. Between 2019 and 2023, new commitments to fossil fuel projects amounted to EUR 325 million, with Egypt, Saudi Arabia and Canada being major recipients. Despite a growing commitment to green finance, the scale and persistence of these carbon-intensive projects pose a challenge to Austria's Paris-alignment ambitions. The study critiques Austria's lag in adopting an overarching net-zero strategy for its export credit system. In response to an EU Council Conclusion from March 2022, Austria devised a Sustainability Strategy of the Export Promotion Procedure in 2023. Though a welcome step, the strategy shows serious deficiencies: Austria embarks on one of the slowest phase-out trajectories among comparable EU peers and allows one of the most wide-ranging sets of fossil exemptions. The current strategy does not define a time-bound road map for achieving a climate neutral portfolio and thus fails to ensure alignment with the Paris Agreement. Austria's approach also includes green finance initiatives like "Exportinvest Green Energy", which offers favourable financial conditions for renewable energy projects. However, a comprehensive approach towards achieving net-zero for the vast majority of its export promotion portfolio is currently missing. This lack of coherence is also evident in the lack of a speedy and science-based roadmap required to phase out high-GHG guarantees fully. Austria's approach is contrasted with other EU countries such as Germany and Sweden, which have adopted more ambitious export credit strategies aligned with climate goals. For instance, Germany's "Climate Policy Sector Guidelines for Export Credit Guarantees" categorize projects into green, white, and red categories based on their contributions to or hindrance of climate goals. Sweden has embraced the "Fossil Free Sweden" initiative, focusing on making the country a leader in fossil-free systems and promoting the export of sustainable technologies. More importantly, both these peers have adopted methods and frameworks for assessing the GHG footprint of projects and for bringing their portfolios progressively more in line with the Paris Agreement.
Keywords: 330; Exportkredit; Außenwirtschaftsförderung; Treibhausgas-Emissionen; Klimaneutralität; Klimapolitik; Österreich